Angola - Staeger, Rob. (Philadelphia : Mason Crest Publishers, 2007)
Examines the historical and current situation of Angolia covering the country's history, geography, government, economy, cultures, and communities.
Geography -- History -- Government -- Economy -- Culture and people -- Cities and communities -- Calendar of festivals -- Recipes -- Glossary -- Project and report ideas -- Chronology.
Includes bibliographical references and index.
Keywords: Angola